2017
DOI: 10.1111/dmcn.13395
|View full text |Cite
|
Sign up to set email alerts
|

Event‐related potential measures of executive functioning from preschool to adolescence

Abstract: ABBREVIATIONS CDAContralateral delay activity [Abstract]Executive functions are a set collection of skills cognitive abilities necessary for behavioural control and regulation and are important for school success. Executive deficits are common across acquired and developmental disorders in childhood and beyond. This review aims to summarize how studies using event-related potential (ERP) can provide insight into mechanisms underpinning the development ofhow executive functions develop in children from preschoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
64
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 118 publications
5
64
1
Order By: Relevance
“…Executive functions are often affected in neurodevelopmental disorders such as ASD (Hill, 2004; Pugliese et al, 2014) and have been shown to have broad and significant implications for everyday life (Miyake and Friedman, 2012; Downes et al, 2017). The prefrontal cortex is regarded as the main brain region involved in executive functions (Friedman and Miyake, 2017), and prefrontal processes seem also to be involved in RRB (Mosconi et al, 2009; Agam et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Executive functions are often affected in neurodevelopmental disorders such as ASD (Hill, 2004; Pugliese et al, 2014) and have been shown to have broad and significant implications for everyday life (Miyake and Friedman, 2012; Downes et al, 2017). The prefrontal cortex is regarded as the main brain region involved in executive functions (Friedman and Miyake, 2017), and prefrontal processes seem also to be involved in RRB (Mosconi et al, 2009; Agam et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The reactive control processes after S2 therefore include conflict monitoring and execution or inhibition of the planned response. The N2 is a negative deflection ~200 ms after S2, and is suggested to reflect the cognitive control necessary for interference suppression and successful inhibition (Donkers and Van Boxtel, 2004; Downes et al, 2017) and thereby conflict monitoring or the degree of experienced conflict (Hammerer et al, 2010). The P3, a positive deflection ~300 ms after both stimuli (S1 and S2), has been suggested to indicate the classification of the stimulus and the selection of responses, and in NoGo trials evaluate the inhibitory process after S2 (Aasen and Brunner, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations